Efekti barijatrijske i metaboličke operacije na aktivnost sinteze žultske kiseline, gena konjugacije enzima i funkciju bukozalne barijere (D-LA, Zonulin-E8) u dijabetičkim bolesnicima: Alterations in Bile Acids before and following Bariatric and Metabolic Surgery for Diabetes - Zhang, Jingjing; Apaer, Shadike; Zhang, Shuo; Liang, Guanyou; Li, Tao; Cao, Xinling (Journal of Medical Biochemistry, 2025)
Objective: To observe the changes of bile acid synthase activity, conjugation enzyme gene and intestinal mucosal barrier function (D-LA, Zonulin, MFG-E8) in patients with type 2 diabetes mellitus (T2DM) after bariatric and metabolic surgery (BMS), and to provide an objective opinion on the clinical optimization of BMS.Methods: 127 patients with T2DM who had received BMS treatment at our hospital from October 2023 to August 2024 were included in the study, and weight loss, glucose-lipid metabolism was detected before surgery and at 6 months after surgery. Furthermore, the study quantified the expression levels of key enzymes involved in bile acid synthesis and conjugation (CYP7A1, CYP27A1, FXR, FGF19) and markers indicative of intestinal mucosal barrier function (D-LA, Zonulin, MFG-E8).Results: After BMS, the patient's weight was significantly reduced and glucolipid metabolism was significantly improved (P